Coexistence of disseminated Kaposi sarcoma and multicentric Castleman disease in an HIV-infected patient under viral suppression. (March 2021) - Lin, I-Fan; Lin, Jiun-Nong; Tsai, Tsung-Heng; Hsu, Chao-Tien; Wu, Yu-Ying; Lai, Chung-Hsu
Coexistence of multicentric Castleman disease and Kaposi sarcoma is rare and might be missed without an experienced pathologists' interpretation. A 46-year-old man had been diagnosed with HIV infection and treated with combination antiretroviral therapy of dolutegravir/abacavir/lamivudine (Triumeq) for one year. The latest viral load was 49 copies/mL and CD4 T-cell count was 192 cells/uL. He was admitted due to fever off and on, splenomegaly, general lymphadenopathy, and severe thrombocytopenia for two months. Biopsy of a purplish skin lesion and gastric tissue showed Kaposi sarcoma. The pathology of inguinal lymph nodes revealed coexistence of Kaposi sarcoma and multicentric Castleman disease. The plasma Kaposi sarcoma herpesvirus viral load was 365, 000 copies/mL. During hospitalization, progressive pancytopenia and spiking fever persisted, and he died of multi-organ failure before completion of chemotherapeutic treatments with rituximab plus liposomal doxorubicin.